New Constructs for the Prediction of Self-Initiated International Mobility: An Exploratory Study. Issue 1 (June 2013) - Thorn, Kaye; Inkson, Kerr; Carr, Stuart
This study aims to explore relationships between the motives for international mobility and observed mobility patterns. The key motives of 2, 608 skilled expatriate New Zealanders were identified as cultural and travel opportunities, career, economics, affiliations, political environment, and quality-of-life. Mobility patterns, described here as the frequency, duration and cessation of mobility and the nature of the destination in terms of development level and cultural distance, were investigated. Desire for cultural and travel opportunities was the dominant motive, and the best predictor of cessation of mobility and development level of the destination. Career motives predicted duration of mobility and cultural difference of the destination. Linking motivation and actual mobility is a novel contribution to the theorisation of self-initiated mobility. Countries and organisations that understand this linkage may ultimately gain competitive advantage.